The Effect of Antibiotic Treatment on the Bacterial Community of the Brown Planthopper and Its Correlation with Rice Virulence - Xiaorong Xu (MDPI AG, 2021)
The prevention and control of planthoppers represent important issues for rice production. Current long-term control methods rely on pesticides, which raise concerns about environmental pollution. Recently, evidence has suggested that bacterial symbionts are important factors influencing the formation of Hemiptera insect biotypes and the selection of host plants for insects, which suggesting that targeting bacterial communities may be an effective alternative method for planthopper control. In this study, we perturbed the bacterial communities of the brown planthopper, Nilaparvata lugens, by feeding antibiotic-treated rice and used RNA-seq to examine the transcriptome of normal rice fed with perturbed BPHs by RNA-seq. Our results showed that the composition of the bacterial communities significantly changed after the perturbation, which was accompanied by changes in distinct biological processes of rice, especially the phenylpropanoid biosynthesis pathway, compared with the effect of the BPH feeding on rice without bacterial communities perturbation. Our work establishes a protocol for bacterial communities perturbation in BPH, demonstrating the link between bacterial community and the responses to BPH feeding and providing new insights into the interaction between BPH and rice.